PROBLEMS OF FUNCTIONING OF THE VENTURE FINANCING MECHANISM IN UKRAINE - Bondarchuk , N.V. (The actual problems of regional economy development, 2022)
The article is devoted to outlining the main problems of the venture financing mechanism in Ukraine. The purpose of the article is to identify problematic aspects of the functioning of venture financing in Ukraine and identify key measures to eliminate them. The research methods used in the process of writing the article involve the use of general scientific and empirical techniques of economics, based on a systematic approach. The article clarifies the essence and role of venture capital as a source of funding for innovation processes. It is stated that venture capital is an effective form of financing and supporting innovation activities of enterprises. However, despite the effectiveness of this form of financing, there are a number of problems that hinder the effective functioning of the venture financing mechanism in Ukraine. Among them are the following: political and economic crisis, imperfect legal framework, underdeveloped innovation infrastructure, lack of available sources of funding, low business culture, insufficient level of venture education, lack of innovation and investment activity in many domestic enterprises. It is noted that the basis of the organization of venture financing is to highlight the phases of the life cycle of the enterprise or product. At each stage of the innovation strategy implementation, it is necessary to develop its own, special strategy, which will be aimed at reducing risk and finding appropriate effective sources of funding. Existing problems should be solved by implementing the following main measures: active government intervention in the development of the venture market; development of targeted state programs to support and stimulate the activities of business angels; creation of a legal basis for venture activity; providing financial support for targeted grants, as well as tax benefits for business angels; reduction of interest rates in banks for the development of small innovative enterprises; creation of regional networks of business angels and expansion of the range of services; state stimulation of the development of business angel associations; increasing the role of education in the field of venture capital by training specialists in educational institutions; use of foreign experience in conducting venture business; education of venture culture among entrepreneurs.